2006
DOI: 10.1139/o06-036
|View full text |Cite
|
Sign up to set email alerts
|

Conservation ofPitx1expression during amphibian limb morphogenesis

Abstract: In contrast to the pattern of limb emergence in mammals, chicks, and the newt N. viridescens, embryos such as Xenopus laevis and Eleutherodactylus coqui initiate pelvic limb buds before they develop pectoral ones. We studied the expression of Pitx1 in X. laevis and E. coqui to determine if this paired-like homeodomain transcription factor directs differentiation specifically of the hindlimb, or if it directs the second pair of limbs to form, namely the forelimbs. We also undertook to determine if embryonic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…In this context, salamander limb regeneration does not occur in the absence of accompanying neural tissue development [61], [62]. Individual genes that are upregulated during fracture healing that have been associated with both neural tissue development and limb development included N-Myc1 (neuronal myc) and the paired-like homeodomain transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, salamander limb regeneration does not occur in the absence of accompanying neural tissue development [61], [62]. Individual genes that are upregulated during fracture healing that have been associated with both neural tissue development and limb development included N-Myc1 (neuronal myc) and the paired-like homeodomain transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, expression was spatially restricted to a small area of the autopod and only found in very early stages. Additionally, Pitx1 expression has been detected at later morphogenic stages in the forelimb of the frog Eleutherodactylus coqui , but not at early limb-bud stages [36]. Authors hypothesized that the forelimb expression of Pitx1 was, in this case, a developmental process peculiar to an organism in which metamorphic and embryonic stages are modified [36], as this species bypasses the tadpole stage and develops limbs within its eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Pitx1 expression has been detected at later morphogenic stages in the forelimb of the frog Eleutherodactylus coqui , but not at early limb-bud stages [36]. Authors hypothesized that the forelimb expression of Pitx1 was, in this case, a developmental process peculiar to an organism in which metamorphic and embryonic stages are modified [36], as this species bypasses the tadpole stage and develops limbs within its eggs. With the addition of our results, with Pitx1 expression in the forelimbs during morphogenesis in P. vitticeps , we highlight the need for further research across a wider range of tetrapods needed to more fully understand evolutionary variation in molecular processes underlying limb morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the homeobox transcription factor Pitx1 has been investigated in tetrapodium; mouse 7,10) , gallus 6,8) , and Xenopus 11) . In these species, Pitx1 is exclusively expressed in the developing hindlimb.…”
Section: Discussionmentioning
confidence: 99%
“…In the regeneration, these roles reversed, namely, Pitx1 relates with the proliferation of tissues without distinguishing between the foreor hindlimb, Tbx genes with limb patterning. Recently, Chang et al 11) reported that Pitx1 was expressed in the development of the forelimb and hindlimb in anuran amphibians, Euletherodactylus coqui. Their observation appears to be incompatible with the gene scheme, but this is not necessarily so.…”
Section: Discussionmentioning
confidence: 99%